Attitudes to affirmative action and the perceived impact of affirmative action programmes in the South African business environment : a comparative study based on race and gender - Wright, Sarah-Ann L (Rhodes University, Faculty of Humanities, Department of Psychology, 1994)
Affirmative action is a sensitive and controversial topic evoking a host of emotional reactions regarding tokenism, reverse discrimination, lowering of standards, quota systems and a disregard for meritocracy (Gatherer & Erikson, 1992). It is also a topic receiving considerable attention in the context of a changing South Africa and will be one of the first steps taken in the labour arena under a new government (Charoux, 1991 ). The goals of the research were firstly, to detail and compare the attitudes of men and women, black and white to affirmative action and secondly, to examine the perceived impact of an affirmative action programme on beneficiaries as well as non-beneficiaries. The research was of a quantitative and qualitative nature, so as to provide the scope and depth desired in such an investigation. A survey was conducted using the data collection techniques of a mail questionnaire (quantitative focus) and individual in-depth interviews (qualitative focus). A pilot study was conducted. The majority of the questions in the questionnaire conformed to the conventions of the Likert Scale (Oppenheim, 1992) and data was analysed using percentile frequencies. Data from the interviews was analysed using the qualitative methods of noting themes and patterns, and clustering as proposed by Miles and Hubem1an (1984). The research was conducted in one large organisation in the infomation services industry, situated in the PWV area. Four key sample groups of white men, white women, black men and black women were used. The results of the research indicate that respondents perceive affirmative action as a policy to primarily address the educational disadvantages of black people in South Africa. Initial attitudes to affirmative action reflected a negative orientation amongst whites but a positive orientation amongst blacks. However, probing into the issues indicated that whilst there is an acceptance of the philosophy of and the need for affirmative action for black people, disagreement existed over which implementation methods of affirmative action (preferential treatment and quota systems) were acceptable and at what interfaces (hiring, training and development, promotion), implementation was acceptable. Attitudes on these various issues were often not divided along racial or gender lines and considerable divergence of attitudes also existed within the sample groups. Gender in affirmative action received less consideration by all four sample groups. Results also indicate that beneficiaries of affirmative action do not perceive affirmative action policies and programmes as stigmatising or negatively affecting their self-esteem. Nonbeneficiaries communicated that affirmative action could result in white resentment if blacks benefit at the expense of whites. Low levels of resentment were evident in the research. The organisation's affirmative action programme was seen to be ineffective due to the lack of communication about the programme, no evidence of its progress in terms of significant representation of blacks at senior levels in company XXX and the inequities that were seen to be still pervading the organisation.
Keywords: Uncatalogued